Auxotrophic Actinobacillus pleurpneumoniae grows in multispecies biofilms without the need for nicotinamide-adenine dinucleotide (NAD) supplementation. Issue 1 (December 2016) - Loera-Muro, Abraham; Jacques, Mario; Avelar-González, Francisco; Labrie, Josée; Tremblay, Yannick; Oropeza-Navarro, Ricardo; Guerrero-Barrera, Alma
Abstract Background Actinobacillus pleuropneumoniae is the etiologic agent of porcine contagious pleuropneumonia, which causes important worldwide economic losses in the swine industry. Several respiratory tract infections are associated with biofilm formation, andA. pleuropneumoniae has the ability to form biofilms in vitro. Biofilms are structured communities of bacterial cells enclosed in a self-produced polymer matrix that are attached to an abiotic or biotic surface. Virtually all bacteria can grow as a biofilm, and multi-species biofilms are the most common form of microbial growth in nature. The goal of this study was to determine the ability ofA. pleuropneumoniae to form multi-species biofilms with other bacteria frequently founded in pig farms, in the absence of pyridine compounds (nicotinamide mononucleotide [NMN], nicotinamide riboside [NR] or nicotinamide adenine dinucleotide [NAD]) that are essential for the growth ofA. pleuropneumoniae . Results For the biofilm assay, strain 719, a field isolate ofA. pleuropneumoniae serovar 1, was mixed with swine isolates ofStreptococcus suis, Bordetella bronchiseptica, Pasteurella multocida, Staphylococcus aureus orEscherichia coli, and deposited in 96-well microtiter plates. Based on the CFU results, A. pleuropneumoniae was able to grow with every species tested in the absence of pyridine compounds in the culture media. Interestingly, A. pleuropneumoniae was also able to form strong biofilms when mixed withS. suis, B. bronchiseptica orS. aureus. In the presence ofE. coli, A. pleuropneumoniae only formed a weak biofilm. The live and dead populations, and the matrix composition of multi-species biofilms were also characterized using fluorescent markers and enzyme treatments. The results indicated that poly-N -acetyl-glucosamine remains the primary component responsible for the biofilm structure. Conclusions In conclusion, A. pleuropneumoniae apparently is able to satisfy the requirement of pyridine compounds through of other swine pathogens by cross-feeding, which enablesA. pleuropneumoniae to grow and form multi-species biofilms.